Non-traditional lipid biomarkers in atherosclerotic cardiovascular disease: pathophysiological mechanisms and strategies to address residual risk - Cong Wang; Haifeng Fu; Hao Xu; Handong Yang; Xinwen Min; Wenwen Wu; Wenwen Wu; Zhixin Liu; Dongfeng Li; Yun Dong; Jun Chen; Jun Chen (Frontiers in Endocrinology)
Atherosclerotic cardiovascular disease (ASCVD) pathogenesis is fundamentally driven by dyslipidemia, characterized by lipid metabolism disorders that facilitate cholesterol deposition within damaged vascular endothelia. This process culminates in atherosclerotic plaque formation and coronary stenosis, ultimately inducing myocardial ischemia. While low-density lipoprotein cholesterol (LDL-C) remains the principal lipid determinant of ASCVD progression, emerging evidence indicates persistent residual cardiovascular risk despite optimal statin-mediated LDL-C control. This review aims to systematically evaluate the contributory role of non-traditional lipid biomarkers in ASCVD pathophysiology and clinical outcomes. Through comprehensive analysis of current research, we examine the biological properties and atherogenic mechanisms of non-conventional lipid particles, epidemiological evidence linking these biomarkers with residual cardiovascular risk, and therapeutic implications of targeting alternative lipid pathways. Particular emphasis is placed on elucidating the pathophysiological interplay between triglyceride-rich lipoproteins, lipoprotein(a), and oxidized phospholipids with vascular inflammation and plaque instability. Furthermore, we critically appraise recent clinical trial data regarding novel lipid-modifying agents and propose future research directions to address current knowledge gaps in residual risk management. This synthesis underscores the necessity of expanding therapeutic strategies beyond LDL-C reduction to achieve comprehensive cardiovascular risk mitigation.